Sophisticated Water Quality and Management System - Ujjal Halder; K. Gopinath; T. A. Manin Thomas; T. Chandru; S. Sandeep; Abishek Prabakaran Ramkumar; B. Prabhu (Research and Developments in Engineering Research Vol. 1, 2023)
Smart water management system is designed to collect data on the distribution, pressure and flow of water in a city or municipality. Our primary goal is to enhance the existing system for managing and addressing urban water requirements. Our objectives include meeting the water needs of urban areas while ensuring sustainability and security, developing a rainwater harvesting system near the water treatment facility, developing a mechanism to identify the source of leaks and water shortages in the supply system, and to reuse waste water from washing machines and kitchen faucets.